De Bezetting revisited. Hoe van De Oorlog een ‘normale’ geschiedenis werd gemaakt die eindigt in vrede - Henkes, Barbara (BMGN - Low Countries Historical Review, 2010)
The Occupation revisited. How Wartime and Repression are converted into ‘Normal’ History At the end of 2009, a new television series about the Netherlands during the Second World War (called The War) was broadcast on Dutch television. Barbara Henkes examines how this audiovisual history can be interpreted and contextualized within Dutch historiography concerning the Second World War and the holocaust. The War was inspired by the wish to take a stand against the viewpoint that was articulated by figures such as the well-known historian, Loe de Jong. During the years 1960-1965 he presented a history of the Netherlands during the war on Dutch national television. This was the first of its kind and was entitled The Occupation. The program depicted the Netherlands as a violated nation whose citizens rose up en masse to oppose the ‘tide of evil’ that swept over them from Germany.De Jong’s national epic, which was also presented in a series of famous books, acquired the status of a master narrative, although it remained somewhat controversial. Soon afterwards other, more ambivalent perspectives on this dramatic episode in Dutch history were presented on Dutch television, with the trailblazing documentary entitled ‘Resolute, but Flexible and in Moderation’ (1974) leading the way. The program makers of The War ignore these alternative narratives and instead present us with a ‘new’ master narrative: their War has Hegelian traits in which coincidence or ‘fate’ determined whether someone collaborated with the Nazi’s, got involved in some form of resistance or carried on with business as usual; a scenario in which ‘human agency’ seems to disappear in the maelstrom of history.